The influence of partial sleep restriction on repeated sprint ability and reaction time in university athletes - Wannell, Benjamin R.; Brunner, Felix M. J.; Lovibond, Zoe; Bond, Bert O. (Frontiers in Sports and Active Living, 2025)
IntroductionFew studies have assessed the influence of acute sleep restriction on repeated sprint ability and reaction time, which are important characteristics of many sports. Additionally, no within-measures study has compared the acute effect of interrupting sleep to an equivalent quantity of sleep lost by going to bed late. This study examined the influence of sleep restriction, achieved by going to sleep late, or by interrupting sleep, on repeated sprint ability and reaction time.MethodsSixteen university team sport players completed 3 conditions in a counterbalanced order; (1) normal sleep (“Control”), (2) 50% sleep loss achieved by going to be late (“Late”), and (3) 50% sleep loss achieved by waking in the middle of their scheduled sleep (“Interrupt”). The following morning, participants completed ten, 8 s all-out cycle sprints, each separated by 52 s recovery. Reaction time to a Go/No-Go test was measured during each recovery interval.ResultsPeak and minimum power output for each repeated sprint interval was always lower in the Late [mean difference (MD) -17 W, P = 0.014, and MD -14 W, P = 0.022] and Interrupt conditions (MD -25 W, P < 0.001 and MD -24 W, P < 0.001), compared to Control. Additionally, average power output was lower across all sprint attempts in Interrupt (MD -14 W, P = 0.007), but not Late (MD -7 W, P = 0.170) compared to Control. Reaction time was never different between conditions.ConclusionOne night of 50% sleep loss can acutely impair repeated sprint ability. Interrupting sleep might be more deleterious than an equivalent amount of sleep lost through late sleep onset.